1998
DOI: 10.1021/jp981860t
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Probe Solubilization in the Headgroup and Core Regions of Micelles:  Fluorescence Lifetime and Orientational Relaxation Measurements

Abstract: Experimental results demonstrate that the fluorescent probes 2-(N-hexadecylamino)-naphthalene-6-sulfonate (HANS) and 2-(N-decylamino)-naphthalene-6-sulfonate (DANS) are solubilized in two distinct regions, that is, the headgroup and core, within micelles of cetyltrimethylammoniumbromide (CTAB), tetradecyltrimethylammoniumbromide (TTAB), dodecyltrimethylammoniumbromide (DTAB), cetyltrimethylammoniumchloride (CTAC), and tetradecyltrimethylammoniumchloride (TTAC). The fluorescence lifetime decays for both chromop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
87
2
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(94 citation statements)
references
References 53 publications
4
87
2
1
Order By: Relevance
“…In this regard two opposing factors can be operative. On one hand, it is known that the ionic concentration in the Stern layer of ionic micelles is high (3-5 mol dm −3 (21)) and this should cause a diminution in the rates of the two processes studied (see Table 1). On the other hand, the polarity of the layer sorrounding the cationic micelles is different from that of pure water (22).…”
Section: Resultsmentioning
confidence: 99%
“…In this regard two opposing factors can be operative. On one hand, it is known that the ionic concentration in the Stern layer of ionic micelles is high (3-5 mol dm −3 (21)) and this should cause a diminution in the rates of the two processes studied (see Table 1). On the other hand, the polarity of the layer sorrounding the cationic micelles is different from that of pure water (22).…”
Section: Resultsmentioning
confidence: 99%
“…Rotational diffusion of two ionic lipophilic fluorophores in alcohol and in SDS, CTAB, and TX-100 micellar environments was reported by Quitevis et al and the study has presented a detailed picture of the structural and dynamical aspects of the probes in micelle-water interfaces [22]. Study of the effect of hydrophobic chain length of surfactants on the dynamical behavior of a fluorophore was started rather recently [19][20][21]. Chakrabarty et al have reported the effect of varying chain length as well as head group of cationic surfactants on the rotational relaxation of coumarin 480 in micellar and mixed micellar environments [19].…”
Section: Introductionmentioning
confidence: 92%
“…Dynamic behavior includes the rotational and/or tumbling motion of the bound fluorophore within the microheterogeneous environments on the picosecond/nanosecond time scale [3,19]. Development of pico-and femtosecond lasers has enabled the researchers to directly probe into the ultrafast relaxation processes in micellar environments by time-resolved fluorescence depolarization techniques [8,14,[19][20][21]. Dutt characterized various components of rotational motion of two structurally similar dyes in Triton X-100 (TX-100) micelle, where the growth of the micelle was induced by the addition of sodium chloride [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(i) fluorescence quenching is diffusion controlled and as such the quenching rate constant, k q , determined from the fits to the quenched decay curve is given by the bimolecular collision rate between probe and quencher, (ii) the larger the size of the micelle, the smaller is the probe-quencher encounter rate; thus k q is inversely proportional to micelle size and has been observed to be so in all TRFQ experiments [20][21][22][23][24][25]. This is proven besides being intuitive.…”
Section: Time-resolved Fluorescence Quenching (Trfq)mentioning
confidence: 99%